Determination of Yield Indicators of Grape Khoraki Varieties in Khorezm Region (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the yield indicators of grape varieties such as Charos, Rizamat Toyifi and Xirmoni were observed, and field observations were made to determine the number of grape heads on one productive branch and the yield coefficient or the ratio of grape heads on the vine bush to all developed branches in these varieties.